Intergenerational mobility and equality of opportunity in primary education - Mikkel Høst Gandil (University of Copenhagen, Department of Economics, 2018)
This thesis is concerned with a possible answer to the question of why we should care about inequality: children. A child can no less choose its parents than it can choose its gender or ethnicity. One cannot fault a child for their choice of school, lack of resources or absence of role models. Therefore, any meritocratic liberal society must grapple with how inequalities persist across generations. In other words, how do parents transmit social status to children? To what extent is such transmission fair, or not, and what can society do to change it? While reading this thesis, these are the questions to have in mind. This thesis is divided into two parts, with four articles in total which, all relate to the question of equality of opportunity and social mobility. The first chapter is self-contained and focuses on the statistical measurement of intergenerational mobility while the remaining three chapters focus on the importance of primary education, inequality in educational input in childhood and its consequences.
Keywords: 330